Platinum(II)‐Coordinated Pyridine‐Functionalized Single‐Wall Carbon Nanotubes and Electron Transport in Their Films. Issue 5 (5th June 2015) - Jombert, Alice S.; Bayazit, Mustafa K.; Coleman, Karl S.; Zeze, Dagou A.
Abstract: Carbon nanotubes (CNTs) are ideal support materials for platinum in fuel cells. However, little is known about the conduction mechanism of Pt‐coordinated CNTs. Herein, a coordination complex of pyridine‐functionalized single‐walled nanotubes (Py‐SWNTs) with Pt (Pt/Py‐SWNTs) was prepared via the ligand exchange reaction between cis ‐[Pt(dmso)2 Cl2 ] and Py‐SWNTs generated by pyridine diazonium salt addition to SWNTs. The presence of Pt in modified SWNTs was confirmed by X‐ray photoelectron spectroscopy (XPS). The N 1s XPS spectra provided evidence of Pt coordination to the pyridine nitrogen atom. Modified SWNTs were further characterized by thermogravimetric analysis coupled with mass spectrometry, ultraviolet‐visible‐near infrared spectroscopy, Raman spectroscopy, and elemental analysis. The electron conduction mechanism of Pt/Py‐SWNT films was best described by a modified quantum tunneling model, identified from a combined analysis of the voltage and temperature dependence of the current. Abstract : Networking with platinum : The dominant conduction mechanism in films of platinum‐coordinated carbon nanotubes using pyridine moieties is presented. The functionalization method favors formation of platinum bridges between the carbon nanotubes, ultimately creating three‐dimensional networks.